Brand Attachment Penggemar dan Idola Melalui Konten Fanatisme - Muhammad Reza Nur Hakim; Cindrakasih, RR Roosita; Rahardjo, Agung; Saeni, Eni; Rahmi, Marlina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The music industry in Indonesia continues to grow. This can be seen from the increasing variety of music that is present in Indonesia. One of these types of music is J-Pop. J-Pop is a type of pop music originating from Japan. JKT48 is one of the J-Pop music groups that carries the concept of idols and has its main base in Jakarta. JKT48 is a sister group or branch group of the Japanese idol group, AKB48. The idol concept owned by JKT48 is the concept of fostered idols. The concept of fostered idols focuses on showing the struggles, processes, and efforts made by members of the fostered idol group in order to become a perfect idol. One form of content created by fans is Kamaniya's Diary. Kamaniya's Diary created a special account on social media X with the username @kamaniya_diary which is dedicated to capturing the moments of a JKT48 member named Greesella Sophina Adhalia. This study aims to determine the fanaticism of the @kamaniya_diary fansite in creating brand attachment between fans and idols through social media content. The method used in this study is qualitative with a case study approach. Research data were obtained through informant interviews and observations as primary data and documentation from informants, articles, previous research, and relevant content as secondary data. The results of this study indicate that the fanaticism of the Kamaniya's Diary fansite is positive fanaticism.